DAMPAK DURASI PENGGUNAAN GAWAI PADA PRESTASI BELAJAR SISWA SDN SUMBON 3 INDRAMAYU - Abellia; Adjie, Eko Kristanto Kunta (Ebers Papyrus, 2024)
The changing times are affecting various fields including technology. Gawai is an electronic device or instrument that has a purpose and function to facilitate the work done by humans. Gadgets can have both positive and negative impacts on their users. This study aims to determine the effect of the duration of gadget use on the learning achievement of 4th and 5th-grade students at SDN Sumbon 3 Indramayu. This study used an observational analytic design with a cross sectional approach. The data obtained was processed using the Chi-Square test. Of the 63 respondents, 23 people used gadgets for more than 3 hours. The results of the Chi-Square test did not find a relationship between the duration of device use and learning achievement of Sumbon 3 elementary school students as evidenced by the results of statistical test research obtained p value of (0.157) > α value (0.05). This study concludes that there is no relationship between the duration of device use and learning achievement of 4th and 5th-grade students of SDN Sumbon 3 Indramayu.